2020
DOI: 10.1017/s1049023x20001193
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Treatment of Acute Pulmonary Edema with Intravenous Bolus and Infusion Nitroglycerin

Abstract: Objective: The study describes the implementation of a prehospital treatment algorithm that included intravenous (IV) bolus (IVB) nitroglycerin (NTG) followed by maintenance infusion for the treatment of acute pulmonary edema (APE) in a single, high-volume Emergency Medical Services (EMS) system. Methods: This is a retrospective chart review of patients who received IVB NTG for APE in a large EMS system in Minnesota and Wisconsin (USA). Inclusion criteria for treatment included a diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 22 publications
2
5
1
Order By: Relevance
“…This study supports the favorable safety profile of prehospital highdose intravenous NTG use for treating AHFS with APE. The frequency of hypotension (1.3%) is similar to values documented in prior prehospital 21,22 and hospital- 10,11,23,24 based studies. Furthermore, this hypotension was transient, with no documented associated arrhythmia or altered mentation.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This study supports the favorable safety profile of prehospital highdose intravenous NTG use for treating AHFS with APE. The frequency of hypotension (1.3%) is similar to values documented in prior prehospital 21,22 and hospital- 10,11,23,24 based studies. Furthermore, this hypotension was transient, with no documented associated arrhythmia or altered mentation.…”
Section: Discussionsupporting
confidence: 80%
“…Our system cost for a single intravenous NTG bottle was approximately $20. Two‐thirds of the patients required only a single 1 mg dose, consistent with prior hospital and EMS studies 11,21,22 …”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Our subgroups analyses extensively failed in detecting any clinical setting with a more favourable setting for IV-NTG use in patients with AHF. Despite many authors have suggested that prompt initiation of IV-NTG in patients with severe pulmonary congestion (presenting in the form of acute pulmonary oedema) could be beneficial especially if it is quickly provided in the prehospital arena [8,[23][24][25], our subgroup analysis considering signs/symptoms of congestion separately according to whether they correspond to pulmonary or systemic congestion did not support this hypothesis, at least with respect to an improvement in patient survival. Similarly, age, sex, CAD as comorbidity and SBP did not have a different impact on the effects of NTG on patient survival.…”
Section: Discussioncontrasting
confidence: 76%